Introduction et synthèse - Achour, Dominique (L'Actualité économique, 1974)
AbstractThe introduction can be considered as a framework for and as a series of critical comments on some of the texts. Viewing Industry, Tourism and Finance as part of the same economic problem, the author brings new elements into the discussion stressing classic weaknesses in the structure of Montreal's economy and emphasizes the fact that his inherent frailty should not be blurred by the satisfactory 1973 conjunctival situation. Two broad policy choices are presented in the form of alternative scenarios: the first is an extrapolation and the other of completely altered industrial policies. The choice of the latter is described as being the only realistic alternative.In the field of tourism, the obvious contradiction between government policies and the facts of the situation stemming from the analysis of tourist behavior is discussed. Concrete proposals are spelled out so as to enhance the regional potential for tourism.The financial sector is evaluated on the efficiency of its performance in mobilizing funds for general investment purposes and also, more specifically, for capital ventures type of financing. Finally, the future of Montreal as a prime financial center is assessed with respect to the national banking structure.